That’s Opera un Nuovo Progetto Artistico e Multimediale - Camera, Maddalena (Archeomatica, 2023)
Together with OperaLombardia, Aedo imagined and created the “That's Opera!” project, a multimedia and spectacular traveling project to change the narration of the world of opera and with the aim of bringing new audiences - especially the younger ones - both to get to know and to inhabit their buildings, and to approach listening to opera in an unprecedented way. Thanks to the construction of sensitive environments with an immersive, multisensory and interactive character, the complexity of the world of opera is told, especially that part that is not seen and which consists in creating and rehearsing the show (backstage and making of opera). What you see on stage is only the emerging tip of the show, its indispensable and magical conclusion. Aedo's main mission consists in enhancing places of culture which, together with the experimentation of new forms and their accessibility, makes it possible to capture and tell the charm and secrets of an art form such as opera. Among the peculiarities of the intervention, in fact, the ability of Aedo, built over time, to use narrative techniques, contemporary artistic, technological and scientific tools and languages stands out, to transmit cultural contents, make them increasingly universally accessible and bring them closer to the public with a surprise of the unreleased.